Wznowienie postępowania w sprawie podziału nieruchomości w związku z zafałszowaniem dowodu - Modrzejewski, Artur K. (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The subject of the article is the analysis of the possibility and circumstances of the resumption of proceedings in connection with the occurrence of the condition specified in Art. 145 § 1 point 1 of the Code of Administrative Proceedings, that is, after conducting proceedings on the division of real estate, the evidence on the basis of which the relevant facts were established, turned out to be false in the proceedings concerning the division of real estate. The article describes the objective and subjective premises and problems related to the necessity to resume the procedure as a result of a false signature of the surveyor placed on the division map.
Keywords: resumption of administrative proceedings; division of real estate; falsification of evidence